Antibacterial Properties of Taro: Extraction, Antibacterial Testing Method, Modification and Application - Atina; Royani, Idha; Assa'idah; Arsyad, Fitri Suryani (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2025)
Taro plants (Colocasia esculenta) contain secondary metabolites identified as antibacterial, antioxidant, anti-inflammatory and anticancer such as alkaloids, glucosides, terpenoids, resins, flavonoids, saponins, phenols, tannins, amino acids. This article discusses various sources related to the potential of taro as an antibacterial, the discussion includes the content of secondary metabolites along with their properties and characteristics, medicinal plant extraction methods, antibacterial testing, applications and future challenges. This review research used data in the form of articles from Scopus, PubMed and Web of Science indexed sources, published between 2015-2024. Data were analyzed descriptively to summarize trends in antibacterial activity and variability across studies. Ethanol extract of taro was screened for secondary metabolite content, antibacterial activity was tested by Kirby Bauer method. Synthesis of antibacterial medicinal plant-based nanoparticles were successfully synthesized with size range between 10-120 nm, with inhibition zones between 11.9-37 mm against pathogens such as S. aureus, E. coli, and L. monocytogenes. Antibacterial nanofibers were synthesized by electrospinning, self-assembly, phase separation, template synthesis, coaxial electrospinning,electrospraying. Characterization used UV-Vis Spectroscopy, FTIR, TEM, XRD, SEM-EDX, HPLC to separate, identify, and quantify bioactive compounds. Common antibacterial mechanisms include inhibition of protein and nucleic acid synthesis, cell membrane damage, and cell structure modification. The application of taro as antibacterial is investigated in pharmaceutical field, industrial field, food field, waste treatment, dentistry field, biomedical field. The development of taro as an antibacterial has great prospects in the pharmaceutical industry, especially as a safe and effective alternative to conventional antibiotics.